1995
DOI: 10.1002/jcp.1041620113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EPC‐1 growth state–dependent expression, specificity, and conservation of related sequences

Abstract: The transcript for EPC-1 (early population doubling level (PDL) cDNA-1) is induced under conditions of growth arrest due to density-dependent contact inhibition and/or serum deprivation in early-passage but not in senescent WI-38 fibroblasts. We have characterized the EPC-1 transcript with respect to its cell-cycle regulation, tissue specificity, and interspecies conservation of related genomic sequences. In low density, quiescent (serum-deprived), early-passage fibroblasts that are stimulated to proliferate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…30 In addition, PEDF has also demonstrated the capacity to promote cell differentiation in neuroblastoma 21 and prostate carcinoma cells, 31 although the mechanism by which this occurs is unknown. In bone, we have previously shown that PEDF is temporally expressed during endochondral bone formation, which suggests that PEDF has a key regulatory role in osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, PEDF has also demonstrated the capacity to promote cell differentiation in neuroblastoma 21 and prostate carcinoma cells, 31 although the mechanism by which this occurs is unknown. In bone, we have previously shown that PEDF is temporally expressed during endochondral bone formation, which suggests that PEDF has a key regulatory role in osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,16 In fibroblasts, PEDF inhibits S-phase entry, whereas its absence allows for DNA replication and cel-lular proliferation. 5,17 Genetic deletion of PEDF in mice supports this role. PEDF-null mice display stromal expansion in several organs, including the pancreas and liver.…”
mentioning
confidence: 89%
“…Although the NH 2 terminus of this protein was blocked, four tryptic peptides showed high homology with the predicted amino acid sequence of human PEDF/early population doubling level cDNA-1 (EPC-1) (8,20). We therefore cloned a cDNA by screening a mouse liver cDNA library with the aid of a probe of 675-base pair nucleotides covering nucleotide positions 443 to 1117 of human PEDF cDNA (8).…”
Section: Identification Of 45-kda Protein As a Collagen-associatedmentioning
confidence: 99%